2004
DOI: 10.1108/02634500410536920
|View full text |Cite
|
Sign up to set email alerts
|

Small business owner‐managers and their attitude to risk

Abstract: Small business risk is a particularly pertinent issue for researchers as there is a strong association between small business owner‐managers/entrepreneurs and risk by virtue of the high failure rates of small firms. The objective of this study was to uncover situations encountered by owner‐managers/entrepreneurs that they perceive to involve an element of risk. More importantly, it seeks to understand how owner‐managers behave when faced with such “risky” situations. A qualitative study was undertaken with own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 29 publications
(36 reference statements)
4
69
1
1
Order By: Relevance
“…We found also owner-managers are able to enter into cooperation for managing risks when they perceived the opportunities to gain a more competitive advantage. The results presented in this paper are consistent with those of Gilmore et al (2004) which stipulate that SMEs often maintain close relationships with existing clients in the hope of doing more business. Delerue and Perez (2009) found that when managers perceive high levels of relational risk, they tend to enter into cooperation relationship and they may manage risks by choosing to forge a relationship with a desirable partner and with that partner to anticipate and deal with risk.…”
Section: Discussion Of Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…We found also owner-managers are able to enter into cooperation for managing risks when they perceived the opportunities to gain a more competitive advantage. The results presented in this paper are consistent with those of Gilmore et al (2004) which stipulate that SMEs often maintain close relationships with existing clients in the hope of doing more business. Delerue and Perez (2009) found that when managers perceive high levels of relational risk, they tend to enter into cooperation relationship and they may manage risks by choosing to forge a relationship with a desirable partner and with that partner to anticipate and deal with risk.…”
Section: Discussion Of Resultssupporting
confidence: 81%
“…By collaboration, the companies can obtain the resources necessary to manage the risk effectively. In the same way, collaboration with competitors can help to prevent the risky operations because sharing information with competitors result in more information about the credit worthiness of prospective customers (Gilmore et al 2004). For Kim and Vonorta (2014) collaboration is frequently used as a risk mitigation strategy in SMEs mostly to adapting with technology, financial and commercial risks.…”
Section: Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kunene (2008), when analysing opportunities and spreading one's risk, an entrepreneur will weigh their risk-taking propensity against an assessment which combines all the various factors that associated with a scenario (Kunene 2008). Gilmore et al (2004) associate the dominant areas of business risk as pertaining to cash flow, company size, entering new markets, and entrusting staff with responsibilities. The entrepreneur's risk-taking traits will help the company to perform.…”
Section: Entrepreneurial Characteristicsmentioning
confidence: 99%
“…Hal ini sesuai dengan pendapat Azid, et al (2008), P3EI (2008, dan Ahmad (1997 Nilai ukhuwah (persaudaraan) yang dikemas dalam ajang silaturahim, yang diterapkan kepada seluruh pemangku kepentingan, telah membentuk jejaring supply chain yang mengarah kepada win-win solution atau azas manfaat bersama yang terus menerus dan jangka panjang. Hal ini sesuai dengan salah satu alat kunci hasil penelitian Gilmore et al (2004) yang mengatakan bahwa dua alat kunci yang digunakan untuk mengelola situasi yang berisiko adalah penggunaan kompetensi manajerial dan jejaring (networking). Loyalitas dan hubungan harmonis antara pemangku kepentingan dengan bisnis di Ponpes Sunan Drajat sebagai dampak dijalinnya jejaring diungkapkan oleh beberapa informan, salah satunya adalah Mr. X yang merupakan santri terbang mengatakan: Temuan lapang ini juga melengkapi khasanah hasil penelitian sebelumnya bahwa pengusaha yang memelihara jaringan kontak dan penggunaan jaringan ini secara positif melalui proses jejaring memberikan manfaat bagi bisnis berskala kecil (Johannisson, 1986;Szarka, 1990).…”
Section: Nilai-nilai Islam Sebagai "Bingkai" Dalam Bisnis Dan Praktikunclassified